Early-stage Growth Dynamics of Senegalia catechu during Restoration of Lowland Flood Plains in Central Nepal - Sapkota, Ramesh Prasad; Khadka, Udhab Raj (Perspectives on Higher Education, 2025)
Use of native species in restoring degraded land is an effective way of restoring integrity of ecosystems. However, there are very few studies assessing growth dynamics of plants in early stages of restoration interventions, and to our understanding there are very limited studies focusing on flood plain inhabiting plant species, particularly Senegalia catechu. The objective of this study, therefore, was to assess the early-stage growth pattern of native riverine S. catechu (locally known as ‘Khair’) in degraded Shakti Khola flood plain (with humans and grazing stressors) of Bara District, Nepal. Three-year growth assessment of S. catechu in the interval of 6 months was performed. Early-stage growth dynamics of S. catechu showed that this species can act as pioneer native species in restoration of lowland Terai flood plains in Nepal. We observed the mean growth ± standard error of basal diameter of S. catechu emerged from broadcast seeding during the first year was 0.43 ± 0.02 cm. During the second and third years, basal diameter reached 2.14 ± 0.10 and 3.76 ± 0.18 cm, respectively. Similarly, during first, second and third years, the mean height of the plant was 39 ± 2.48, 133 ± 5.95 and 260.56 ± 11.22 cm, respectively. The results indicate that the attempt was successful in establishing S. catechu seedlings and saplings in the sandy and nutrient poor flood plains areas. Future attempts should focus on establishing other co-existing native species and develop regional floodplain management strategy and co-benefit local communities.